Dragonsdale - Drake, Salamanda (New York : Chicken House/Scholastic, 2007)
Cara yearns to ride her beloved Skydancer, a rare Goldenbrow dragon, but her father refuses to permit her to fly and she must be content with mucking out stalls and helping raise young dragons at the famed stud and training farm known as Dragonsdale.
900
Keywords: Dragons -- Juvenile fiction; Fantasy fiction